Involvement of Cyclophilin D and Calcium in Isoflurane-induced Preconditioning. (December 2015) - Teixeira, Geoffrey; Chiari, Pascal; Fauconnier, Jeremy; Abrial, Maryline; Couture-Lepetit, Elisabeth; Harisseh, Rania; Pillot, Bruno; Lacampagne, Alain; Tourneur, Yves; Gharib, Abdallah; Ovize, Michel
Abstract : Background: The mitochondrial permeability transition pore (PTP) has been established as an important mediator of ischemia–reperfusion–induced cell death. The matrix protein cyclophilin D (CypD) is the best known regulator of PTP opening. Therefore, the authors hypothesized that isoflurane, by inhibiting the respiratory chain complex I, another regulator of PTP, might reinforce the myocardial protection afforded by CypD inhibition. Methods: Adult mouse or isolated cardiomyocytes from wild-type or CypD knockout (CypD-KO) mice were subjected to ischemia or hypoxia followed by reperfusion or reoxygenation. Infarct size was assessed in vivo . Mitochondrial membrane potential and PTP opening were assessed using tetramethylrhodamine methyl ester perchlorate and calcein–cobalt fluorescence, respectively. Fluo-4 AM and rhod-2 AM staining allowed the measurement, by confocal microscopy, of Ca 2+ transient and Ca 2+ transfer from sarcoplasmic reticulum (SR) to mitochondria after caffeine stimulation. Results: Both inhibition of CypD and isoflurane significantly reduced infarct size (−50 and −37%, respectively) and delayed PTP opening (+63% each). Their combination had no additive effect (n = 6/group). CypD-KO mice displayed endogenous protection against ischemia–reperfusion. Isoflurane depolarized the mitochondrial membrane (−28%, n = 5), decreased oxidative phosphorylation (−59%, n = 5), and blunted the caffeine-induced Ca 2+ transfer from SR to mitochondria (−22%, n = 7) in the cardiomyocytes of wild-type mice. Importantly, this transfer was spontaneously decreased in the cardiomyocytes of CypD-KO mice (−25%, n = 4 to 5). Conclusions: The results suggest that the partial inhibitory effect of isoflurane on respiratory complex I is insufficient to afford a synergy to CypD-induced protection. Isoflurane attenuates the Ca 2+ transfer from SR to mitochondria, which is also the prominent role of CypD, and finally prevents PTP opening. Abstract : This study demonstrates that protections afforded by isoflurane and cyclophilin D inhibition are not additive. The partial inhibitory effect of isoflurane on respiratory complex I is insufficient to afford a synergy to cyclophilin D–induced protection.